2018
DOI: 10.1111/jpi.12505
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of melatonin in plant‐host resistance and pathogen suppression in cucurbits

Abstract: Since the 1950s, research on the animal neurohormone, melatonin, has focused on its multiregulatory effect on patients suffering from insomnia, cancer, and Alzheimer's disease. In plants, melatonin plays major role in plant growth and development, and is inducible in response to diverse biotic and abiotic stresses. However, studies on the direct role of melatonin in disease suppression and as a signaling molecule in host-pathogen defense mechanism are lacking. This study provides insight on the predicted biosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 91 publications
3
89
0
Order By: Relevance
“…Our current data update the role of PTEN in mitochondrial apoptosis and introduce the role of PTEN in mitophagy regulation for the first time (Mandal, Suren, Ward, Boroujerdi, & Kousik, 2018;Poreba et al, 2019). This finding provides insight into the mechanism by which PTEN deletion preserves mitochondrial function and structure.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our current data update the role of PTEN in mitochondrial apoptosis and introduce the role of PTEN in mitophagy regulation for the first time (Mandal, Suren, Ward, Boroujerdi, & Kousik, 2018;Poreba et al, 2019). This finding provides insight into the mechanism by which PTEN deletion preserves mitochondrial function and structure.…”
Section: Discussionsupporting
confidence: 61%
“…PTEN modulates (Mukherjee et al, ; Owino et al, ) ROS production and regulates mitochondrial ATP production (Nicklas et al, ), affecting cell proliferation and the vulnerability of kidney tubules and myocytes to stress (Y. Wang, Chen, et al, ). Our current data update the role of PTEN in mitochondrial apoptosis and introduce the role of PTEN in mitophagy regulation for the first time (Mandal, Suren, Ward, Boroujerdi, & Kousik, ; Poreba et al, ). This finding provides insight into the mechanism by which PTEN deletion preserves mitochondrial function and structure.…”
Section: Discussionmentioning
confidence: 55%
“…tomato ( Pst ) DC3000 (Shi et al ., ,c). Melatonin alters the expression of genes involved in both PAMP‐mediated and ETI‐mediated defense in watermelon leaves during Phytophthora capsici infection (Mandal et al ., ). Therefore, we propose that melatonin mediates broad‐spectrum pathogen resistance in plants via diverse mechanisms, possibly depending on the disease mechanism of the pathogen.…”
Section: Discussionmentioning
confidence: 97%
“…Plant melatonin also alleviates abiotic stresses from cold, heat, drought, salt, to heavy metals (Shi et al ., ,d; Wei et al ., ; Li et al ., ,c; Ding et al ., ). Studies have implicated melatonin in plant immunity (Yin et al ., ; Lee et al ., ; Shi et al ., ,d; Mandal et al ., ), but the underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Qian, et al [42] reported on the participation of sugar and glycerol in melatonin-associated protection against (Pst) DC3000 through SA-and NO-dependent pathways in Arabidopsis [42]. Recently, exogenous melatonin treatment was found to activate ETI-and PTI-associated genes in watermelon and Arabidopsis according to transcriptomic data [40,41]. All of the bactericidal activities of melatonin, the related mechanisms involved, and the resulting constructive effects in plants are summarized in Table 2 and Figure 1.…”
Section: Melatonin Bioactivity Against Bacteriamentioning
confidence: 99%